2013
DOI: 10.3390/molecules18043927
|View full text |Cite
|
Sign up to set email alerts
|

Volatile and Amino Acid Profiling of Dry Cured Hams from Different Swine Breeds and Processing Methods

Abstract: The flavor of dry cured ham explains the high appreciation of this product and it determines consumer acceptance. Volatile compounds provide valuable information about the odor and sensory quality of dry cured hams. Since amino acids are the origin of some volatile compounds of dry cured ham, the volatile and amino acid compositions of forty-one dry cured hams from Spain and France were determined to establish associations between them. The samples included different pig breeds (non Iberian vs. Iberian), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
46
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 43 publications
9
46
0
1
Order By: Relevance
“…Nonanal comes from the oxidation of oleic acid that is the most abundant unsaturated fatty acid in hams (Pham et al 2008) and contributes to flavour with sweet and fruity aroma (Nunes et al 2008). The most abundant saturated aldehydes in Iberian dry-cured ham were octanal, nonanal and hexanal (García-González et al 2013) which is similar with the results of this study. In general, saturated aldehydes contributed to aroma with sensory descriptors such as green/grassy (hexanal), hamlike/fatty (heptanal) and meat-like/fruity (octanal) although with different intensity depending on the breed (Tjener and Stahnke 2007).…”
Section: Analysis Of Volatile Compoundssupporting
confidence: 82%
See 3 more Smart Citations
“…Nonanal comes from the oxidation of oleic acid that is the most abundant unsaturated fatty acid in hams (Pham et al 2008) and contributes to flavour with sweet and fruity aroma (Nunes et al 2008). The most abundant saturated aldehydes in Iberian dry-cured ham were octanal, nonanal and hexanal (García-González et al 2013) which is similar with the results of this study. In general, saturated aldehydes contributed to aroma with sensory descriptors such as green/grassy (hexanal), hamlike/fatty (heptanal) and meat-like/fruity (octanal) although with different intensity depending on the breed (Tjener and Stahnke 2007).…”
Section: Analysis Of Volatile Compoundssupporting
confidence: 82%
“…However, the low odour threshold of 1-octen-3-ol indicated that it contributed strong mushroom aroma to almost all the hams. The concentration of this compound significantly arose as the amount of curing salt increases, which explained the differences between samples (García-González et al 2013). Therefore, 1-octene-3-ol was the most abundant alcohol in Dalmatian smoked dry-cured ham due to the high salt content.…”
Section: Analysis Of Volatile Compoundsmentioning
confidence: 94%
See 2 more Smart Citations
“…These characteristics of local breeds are very relevant for humans living in developing countries where local domestic animals are an important source of protein. Local breeds are also appreciated in developed countries for their cultural heritage value, and as producers of traditional and high quality meat products [4, 5]. Increasingly, local heritage breeds are recognized for their potential in sustainable or organic food production systems.…”
Section: Introductionmentioning
confidence: 99%